THE CHALLENGE OF COLLABORATIVE TEACHING IN THE INCLUSIVE SCHOOL - COSTA-RENDERS, Elizabete Cristina (2024)
This article presents the results of a research that questioned the challenges of school inclusion, especially considering the demands of collaborative teaching. The question was: what are the contributions of collaborative teaching to school inclusion? The general objective of this investigation was to identify and problematize how collaborative teaching between specialist teachers and regent teachers has taken place in the process of school inclusion. It was a narrative research, the instruments were pedagogical letters and conversation wheel. The research participants were four regent teachers and two specialist teachers. The results showed that collaborative teaching in its true conception does not yet occur in most school units, however there are several collaborative actions. It was also pointed out that it is necessary to provide professionals with time and space for these interactions.